Association between diastolic dysfunction and future atrial fibrillation in the Tromsø Study from 1994 to 2010. Issue 16 (13th May 2015) - Tiwari, Sweta; Schirmer, Henrik; Jacobsen, Bjarne K; Hopstock, Laila A; Nyrnes, Audhild; Heggelund, Geir; Njølstad, Inger; Mathiesen, Ellisiv B; Løchen, Maja-Lisa
Abstract : Objective: To investigate the association between echocardiographic measurements with emphasis on diastolic dysfunction and risk of atrial fibrillation (AF) in a population-based cohort study. Methods: We followed 2406 participants from the Tromsø Study from 1994 to 2010. Left atrial (LA) size and mitral Doppler indices as measured by echocardiography were used for evaluating diastolic dysfunction. Information concerning age, systolic blood pressure, height, heart rate, body mass index, total and high-density lipoprotein cholesterol, self-reported use of alcohol, smoking, coffee, physical activity, antihypertensive treatment, prevalent coronary heart disease, valvular heart disease, heart failure, hypertrophy, diabetes and palpitations were obtained at baseline. The outcome measure was clinical AF, documented by an ECG. Results: AF was detected in 462 subjects (193 women). Mean age at baseline was 62.6 years. Incidence rate of clinical AF was 12.6 per 1000 person-years. In multivariable Cox proportional hazards regression analysis, moderately enlarged LA was associated with 60% (95% CI 1.2 to 2.0) increased risk of AF. Severely enlarged LA had HR for AF of 4.2 (95% CI 2.7 to 6.5) with p value for linear trend <0.001, and the association was similar in both sexes. Abnormal mitral Doppler flow adjusted for predictor variables did not show a statistically significant association with AF risk. However, when LA size was also adjusted for, the risk of AF increased by 30% (95% CI 1.0 to 1.6). Conclusions: Our findings suggest that enlarged LA as a measure for diastolic dysfunction is a significant risk factor for AF in both sexes, and adding measures of abnormal diastolic flow increased the predictive ability significantly.